2022
DOI: 10.1093/jncics/pkac052
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Effects of Adjuvant Therapy on Inflammatory Markers in Breast Cancer Patients

Abstract: Background Inflammation contributes to poor behavioral, functional, and clinical outcomes in cancer survivors. We examined whether standard cancer treatments—radiation and chemotherapy—led to acute and persistent changes in circulating markers of inflammation in breast cancer patients. Methods One-hundred and ninety-two women diagnosed with early-stage breast cancer provided blood samples before and after completion of radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…We found that IL-6, IL-10, and TNF-α had a direct relationship with cognition in survivors and controls, findings that parallel prior work by others. 13,[18][19][20][22][23][24][25]39,40 The modest but nonsignificant mediation effect of IL-10, which has regulatory anti-inflammatory and B cell stimulatory activity, may reflect the dynamic nature of its secondary responses to increased proinflammatory markers. 41 IFN-γ, which is produced during immune activation and antiviral responses, and IL-8, which is a chemoattractant for neutrophils, were unrelated to cognition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We found that IL-6, IL-10, and TNF-α had a direct relationship with cognition in survivors and controls, findings that parallel prior work by others. 13,[18][19][20][22][23][24][25]39,40 The modest but nonsignificant mediation effect of IL-10, which has regulatory anti-inflammatory and B cell stimulatory activity, may reflect the dynamic nature of its secondary responses to increased proinflammatory markers. 41 IFN-γ, which is produced during immune activation and antiviral responses, and IL-8, which is a chemoattractant for neutrophils, were unrelated to cognition.…”
Section: Discussionmentioning
confidence: 99%
“…This will be important to examine further, because others have found that radiotherapy and/or chemotherapy induce cellular damage that increases peripheral inflammation and cognitive problems and that HER2-positive cancers are associated with cognitive problems even before treatment. 19,24,38 Fifth, because we added blood collection to an already established cohort, not all survivors had plasma data before systemic therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The data are part of a larger longitudinal study investigating cancer-related fatigue in women with stage 0-IIIA breast cancer assessed prior to starting adjuvant or neoadjuvant treatment, approximately 2 weeks after completion of radiation and/or chemotherapy in those who received it, and 6, 12, and 18 months later. Six pro-inflammatory markers were assessed in plasma (tumor necrosis factor–α, interleukin [IL]–6, IL-8, soluble tumor necrosis factor receptor type II, interferon-γ, and C-reactive protein [CRP]) in 192 (71%) of the RISE participants, with the primary aim of evaluating the impact of radiotherapy and chemotherapy on the inflammatory markers ( 6 ). When considered broadly, the findings support the contention that inflammation can be sustained above baseline levels for months to years following cancer treatment despite tending to decline posttreatment.…”
mentioning
confidence: 99%